In Vivo Evaluation of (−)-Zampanolide Demonstrates Potent and Persistent Antitumor Efficacy When Targeted to the Tumor Site - Leila Takahashi-Ruiz; Joseph D. Morris; Phillip Crews; Tyler A. Johnson; April L. Risinger (Molecules, 2022)
Microtubule-stabilizing agents (MSAs) are a class of compounds used in the treatment of triple-negative breast cancer (TNBC), a subtype of breast cancer where chemotherapy remains the standard-of-care for patients. Taxanes like paclitaxel and docetaxel have demonstrated efficacy against TNBC in the clinic, however new classes of MSAs need to be identified due to the rise of taxane resistance in patients. (−)-Zampanolide is a covalent microtubule stabilizer that can circumvent taxane resistance in vitro but has not been evaluated for in vivo antitumor efficacy. Here, we determine that (−)-zampanolide has similar potency and efficacy to paclitaxel in TNBC cell lines, but is significantly more persistent due to its covalent binding. We also provide the first reported in vivo antitumor evaluation of (−)-zampanolide where we determine that it has potent and persistent antitumor efficacy when delivered intratumorally. Future work on zampanolide to further evaluate its pharmacophore and determine ways to improve its systemic therapeutic window would make this compound a potential candidate for clinical development through its ability to circumvent taxane-resistance mechanisms.